First cow / [videorecording (DVD)] - Reichardt, Kelly; Magaro, John, 1983-; Lee, Orion; Auberjonois, René, 1940-2019; Jones, Toby, 1966-; Bremner, Ewen; Shepherd, Scott, 1969 or 1970-; Farmer, Gary, 1953-; Gladstone, Lily; Raymond, Jonathan (Lionsgate, 2020)
The quiet, skilled cook Otis "Cookie" Figowitz has traveled west into Oregon with a group of aggressive fur trappers. While living in the territory, Cookie finds develops a frienship with the Chinese immigrant King-Lu, who's also come to Oregon to seek his fortune. Soon the two collaborate on a successful business of selling baked goods in their frontier outpost--but Cookie and Lu's business plan is dependent on stealing milk from the first cow imported into the territories, a nerve-wracking venture that eventually puts them at deadly odds with the cow's wealthy and politically connected owner.